2007
DOI: 10.1002/pssb.200675602
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and recombination in InAs quantum dots

Abstract: In this paper we discuss recent developments in the study of the temperature dependence of the optical properties of InAs/ GaAs quantum dots and the mechanisms involved in the relaxation and recombination from InAs/AlAs quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Thermal quenching then results from nonradiative recombination processes that occur in one or several of those higher-energy states. [4][5][6][7][8][9][10][11][12][13][14][15][16] Even though both measurements and theoretical modeling appear straightforward, there remains to this day significant differences and apparent contradictions in the interpretation of the results published by different groups over the last decade.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal quenching then results from nonradiative recombination processes that occur in one or several of those higher-energy states. [4][5][6][7][8][9][10][11][12][13][14][15][16] Even though both measurements and theoretical modeling appear straightforward, there remains to this day significant differences and apparent contradictions in the interpretation of the results published by different groups over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…As temperature is increased, redistribution of the carrier population occurs toward the low-energy tail of the QD energy distribution. [4][5][6]9,11 When the full width at half maximum ͑FWHM͒ of the emission of the ensemble of QDs is much smaller than any expected activation energy, the QD energy distribution is often represented by a ␦ function. The solution of the thermal rate equations in steady state for the ensemble PL intensity I then gives…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Warming the sample sufficiently causes a thermal redistribution of carriers from higher-energy (smaller) dots to lower-energy (bigger) dots via the wetting layer. This is manifested by the PL energy decreasing faster with increasing temperature than is expected from the change in the band gap [41][42][43]. Nuytten and co-workers studied the temperature dependence of the PL energy in magnetic field under such conditions [40], and concluded that for dots where such a redistribution of carriers occurs, in the presence of magnetic field, the contribution of the smaller dots (high-energy dots) to the PL energy becomes greater relative to the bigger dots (lowenergy dots) as the field increases.…”
Section: Bohr Radius Bubble Plotmentioning
confidence: 92%
“…quantum computing devices. The fabrication techniques of the SACQDs are not a simple formation mechanism but appears to be difficult and not easy to be controlled (Barabási & Stanley, 1995;Darula & Barabási, 1997;Daudin et al, 1997;Dawson et al, 2007;Eaglesham & Cerullo, 1990;Lee et al, 1998;Rastelli et al, 2005;Tersoff, 1995;Tu & Tersoff, 2007). The various parameters (e.g.…”
Section: Self-assembled Qdsmentioning
confidence: 99%